Construction Safety Planning Method Based on Project Loan ( Lot 8 Jarit-Puger Road Project Case Study) - Galuh Tiara Dewi; Fredy Kurniawan (NAROTAMA UNIVERSITY, Indonesia, 2022)
The development of infrastructure in Indonesia has increased with the implementation of national strategic projects. With the increasing growth of infrastructure development in Indonesia and the increasing number of work-related accidents on the site. Accidents at work occur because of the lack of attention to implementation and monitoring. The success of the project is not measured merely in terms of performance, but in the application of occupational safety and health to a project and becomes one of the benchmarks for success. To control the implementation of Occupational Safety and Health in the project, a Construction Safety Plan is required, while compiled in the Construction Safety Plan document included in the Construction Safety Management System document. The research methodology used data collected in the field. Collect data from implementation case studies and comparisons related to construction safety planning documents against applicable regulations through field observations using documentation, questionnaires, observations and documentation methodology. Based on the analytical results conducted in this study, there are five elements to prepare the construction safety plan documents. Reduce the number of work-related accidents by planning, monitoring, and evaluating work-related accidents. There is an expectation that further analysis of the factors that cause work accidents by adding research objects to reduce work accidents in construction projects. For the analysis, the authors hope that the causes of industrial accidents will be more detailed by adding research topics to reduce accidents in construction projects.